Managing fraud risk : a practical guide for directors and managers - Giles, Steve, 1957- (Chichester, West Sussex, United Kingdom : John Wiley & Sons Ltd, 2012)
"A strategic, practical, cost-effective approach to fraud preventionIn troubled economic times, the risk of fraud and financial crime increases. In our post credit crunch environment, new laws and tougher penalties for financial crime mean that if you are in business, you have a responsibility to help fight fraud.However, to design effective, proportionate fraud controls for your business, you need a complete picture of all the risks. Managing Fraud Risk shows you where to look for fraud, setting out a route-map for finding and fighting fraud risks in your business, with the practical, strategic advice you need.Combining the latest theory with forensic risk analysis, this book reveals how you can provide assurance to your Board and stakeholders. Practical examples are used to clearly show cost-effective techniques for preventing and detecting business fraud. An innovative fraud awareness quiz enables you to easily apply the theories and principles. Answers questions such as: Who commits more fraud: men or women? How many of your employees are prepared to falsify documents? Essential information to ensure your procedures are sufficient to meet compliance with new international legislation increasing the liability of directors and managers in cases of fraud and corruption Takes a new perspective from the point of view of business risk, making it unique to other texts that take only an auditing, investigative, or specialist approach This route-map is essential reading to help you navigate the complex landscape of business fraud"--
"NEW APPROACH: strategic, risk-based, practical, cost-effective, written from a business risk, rather than an investigation or audit perspective"--
Responsibility -- Meaning -- People -- Risk -- Governance -- Controls -- Prevention -- Detection --Investigation -- Ethics.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Fraud -- Prevention; Commercial crime -- Prevention; Risk management; BUSINESS & ECONOMICS / Auditing; Commercial crimes -- Prevention; Fraud -- Prevention; Risk management; Electronic books